THICKNESS INFLUENCE ON ABSORBING PROPERTIES OF STRATIFIED COMPOSITE MATERIALS - IULIANA IAȘNICU (STAMATE) (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2015)
Plates known as sound absorbing materials: textiles recovered fabrics plus polyethylene are made layered composite material intended to be used to encapsulate industrial engines, as sources of noise in the production departments. Influence of thickness sound-absorbing material can be supported by the values obtained for the absorption coefficient, but it can be studied as a study case in the anechoic chamber, where the sound pressure level is measured with a sound level meter. Cases captured: a free engine; the engine placed in a metallic cube and motor inserted; metal cube that was doubled separately with one material and then with the composite material proposed. For each situation are eight determinations on the perimeter of a circle with a radius of one meter from the source of the noise. Plot a graph of experimental results that support the idea: greater thickness of the layer of material will cause a better absorption of noise.